Which Factors Predict Consumer Willingness to Ride in Driverless Vehicles?. (September 2018) - Anania, Emily C.; Mehta, Rian; Marte, Daniel; Rice, Stephen; Winter, Scott R.
Driverless vehicles are already in development and predicted to enter the market in a matter of years. Previous research centered on driverless vehicles has aimed to gauge whether or not consumers are willing to ride in different types of driverless vehicles. However, the current research investigated different variables that may influence consumer willingness to ride in a driverless vehicle. Variables investigated included demographic variables, emotions, and other information collected by researchers based on a theoretical framework. Participants responded to a willingness to ride scale, as well as different questionnaires and demographic surveys. Out of thirteen possible predictor variables, three were significant: happiness, fear, and value. In a regression model, these three variables accounted for 77% of the variance in the data. These findings contribute to the knowledge of consumer perceptions, as well as inform the current market. Implications for future research, as well as limitations, are also discussed.